Hepatitis B immunity and vaccine completion among adults at increased risk for hepatitis B infection in Zambia - Enock Syabbalo; Sydney Mpisa; Michael J. Vinikoor; Mercy Wamundila; Likando Munalula; Taonga Musonda; Ruth Phiri; Paul Kelly; Chloe Thio; David L. Thomas; Edford Sinkala (PLoS ONE, 2026)
Background Because of its low cost and lasting effects, hepatitis B virus (HBV) vaccination of adults in Africa could significantly contribute to viral elimination. Among at-risk adult populations there are few data to inform vaccine implementation, including on pre-existing immunity and vaccine uptake. We serologically profiled adults with specific risk factors for HBV infection in urban Zambia and evaluated their uptake of vaccine. Methods At a tertiary hospital in Lusaka, we recruited hepatitis B surface antigen-negative adult (age 18+) contacts to people with chronic HBV, health workers (HCWs), and people with HIV (PLWH). After we jointly collected blood and gave the first HBV vaccine dose (blind to the full serological profile), we called back those whose results showed insufficient surface antibodies (anti-HBs) to complete the 3-dose series at 1 and 6 months, and we reimbursed transport costs. Stratified by group, we described the proportions of participants with past vaccination, resolved infection (anti-HBc-positive regardless of anti-Hbs status), isolated core antibodies (anti-HBc-positive and anti-HBs-negative), and neither antibody. We described the correlates of resolved infection. We described completion of the vaccine series in anti-HBs-negatives. In those with isolated core antibodies, we explored the incidence of an anamnestic response based on post-first-dose anti-HBs > 10 IU/ml and>= 1-log increase from baseline. Results 616 adults (median age, 32.2 years, IQR [26.7–43.8]; 61.2% women) enrolled, including 333 contacts, 213 HCWs, and 70 PLWH. Half had neither antibody, including 68.5% of health workers. Prior vaccination was seen in 8.3% overall, including 11.3% of HCWs. Resolved infection was present for 39.3% and was more prevalent with increased age and among contacts. Isolated core was present in 59 (9.6% overall and 24.7% of those with resolved infection) participants. Among the 383 participants eligible for vaccination, 377 (98.4%) received 1 dose, 190 (49.6%) received 2 doses, and 54 (14.1%) completed the series. Among 18 individuals with isolated core antibodies, none had detectable HBV DNA, and 9 (50%) had an anamnestic response. Discussion Most adults at risk for HBV in Lusaka, Zambia, had inadequate immunity, which could undermine HBV elimination. High resolved infection rate in contacts supports the role of index testing in HBV case finding. Low vaccine completion, despite vaccine access and addressing transportation costs, was striking and underscores the need for integrated behavioral science approaches to improve implementation of this potentially cost-effective intervention. Low rates of anamnestic response in people with anti-HBc-positivity should be further studied in Africa.